Fatores associados a duração do aleitamento materno exclusivo no município de João Pessoa - PB - Silva, Lais Kisly Costa (2021)
Breastfeeding is associated with the highest standard of health, a complete and ideal source of nutrition for the infant, and must be exclusive until the sixth month of life and supplemented until two years of age or more. The practice of breastfeeding triggers positive outcomes related to the health of mother and child in the long and short term, contributing to a reduction in the risk of obesity, overweight, growth failure, food allergies/intolerances and increased intellectual performance in children. The aim of the study was to identify the factors related to exclusive breastfeeding and the consequences of this practice in a cohort of mothers from João Pessoa/PB. This is a prospective cohort study, carried out from 2018 to 2020, involving 162 women from the gestational period until their children completed around six months of age. Sociodemographic data of the family, prenatal care, child feeding, food security situation, quality of life and level of anxiety of the woman were collected. Data were exported to the SPSS statistical program, survival analysis was used by the Kaplan-Meier method to estimate the median duration of exclusive breastfeeding (AMEX). The Cox multiple regression model was used to verify the independent factors that increased the median duration of AMEX. Most women were young, with high school education level, had an occupation outside the home and reported the presence of a partner. During the first interview it was observed that 48.6% of pregnant women had better factors associated with quality of life, high trait anxiety was 63.5% and state anxiety 73.8%. Regarding the median of exclusive breastfeeding, it was 120 days (95% CI: 96.6 – 143.4). The variables associated with shorter duration of exclusive breastfeeding were: not receiving guidance during the prenatal period on breastfeeding (HR: 1.67), having difficulty breastfeeding (HR: 1.58) and children who use a pacifier (HR: 1.64), becoming risk groups for early weaning. These results showed that receiving guidance from health professionals during prenatal care had an impact on the longer duration of exclusive breastfeeding and that such guidance should be continued after the baby is born. However, it is clear that there is a need for greater actions aimed at reducing difficulties during breastfeeding, as the support received by mothers was insufficient after the child's birth.